Effect of 4-benzylidenamino-5-phenyl-4Н-1,2,4-triazole-3-thiones and salts of 2-(4-amino-5-phenyl-4Н-1,2,4-triazole-3-ylthio)acetic acid on central component of nociceptive system - Ye. S. Pruhlo (Zaporozhye State Medical University, 2016)
Aim. To study the effect of 4-benzylideneamino-5-phenyl-4H-1,2,4-triazole-3-thiones and salts of 2-(4-amino-5-phenyl-4H-1,2,4-triazole-3-yltio)acetic acid on central component of nociceptive system on condition of thermal stimulation of limbs of rats, and also to explore patterns related with the chemical structure and pharmacological activity of 1,2,4-triazole derivatives. Materials and methods. The newly synthesized derivatives of 4-benzylideneamino-5-phenyl-4H-1,2,4-triazole-3-thiones and salts of 2-(4-amino-5-phenyl-4H-1,2,4-triazole-3-ylthio)acetic acid (Table. 1) have been used in the studies. General toxic effect and acute toxicity of compounds had been previously studied by express method of V.B. Prozorovskiy to determine the conditions of test-substance dosing [4]. The study has been conducted on a group of non-linear white rats of both sexes weighing 185-229 g. Results. The compound that is close to the reference medication - analgin, by its activity, has been revealed. This compound exhibits analgesic activity at considerably lower doses than the proposed reference medication. Conclusions. Some relations between chemical structure and pharmacological activity of the investigated 1,2,4-triazole derivatives have been established. Thus, condensation of 4-amino-5-phenyl-4H-1,2,4-triazole-3-thione with 4- hydroxybenzaldehyde causes almost no effect on analgesic action of starting thione and 4-(4-hydroxybenzylideneamino)-5-phenyl-4Н-1,2,4-triazole-3-thione, whereas the replacement of 4-hydroxybenzylideneamino substituent by 2-hydroxybenzylideneamino substituent reduces the sensitivity of rats to thermal stimulus. The replacement of morpholine cation in the molecule of morpholine salt of 2-(4-amino-5-phenyl-4H-1,2,4-triazole-3-ylthio)acetic acid by piperidinium cation leads to sudden appearance of analgesic activity.